Pengaruh Semangat Kerja Terhadap Produktivitas Kerja Karyawan Bagian Produksi Pada PT. Semen Tonasa Kabupaten Pangkep - Irfan Irfan; Kamaruddin Kamaruddin; Baharuddin Baharuddin (Jurnal Kajian dan Penelitian Umum, 2023)
This research aims to determine the effect of work enthusiasm on employee work productivity at the company PT. Semen Tonasa District. Pangkep. The method used in this research is a quantitative method with the number of respondents being 75 employees who were used as samples using a sampling technique, namely using a saturated sample. The analysis used in this research is a simple linear regression test. The results of simultaneous testing of the education level variable have a positive and significant effect on the work productivity variable as proven based on the results of the simultaneous test with a significance value of f<α (0.000<0.05). The results of partial testing of the education level variable have a positive and significant effect on the work productivity variable with a significance value of f<α (0.000<0.05).